Evaluation of water table influence to slop stability / Muhamad Syafien Kamaruzzaman - Kamaruzzaman, Muhamad Syafien (2019)
Problem based a huge tragedy on the slope failure in Cameron Highland was spread in Malaysia media and reported about seven peoples were found dead and two were in seriously injured in this tragedy. Based on these tragedies, slope failure seems to be one a huge disaster in this country. Considering the issues, this study utilizes erosion induced slope failure to categorize a slope hazard at Penang Hill, Pulau Pinang. This project aims to determine the water table of soil content and effected of soil-water characteristics to slope stability which engage with water table in soil content and analyse slope stability using GPR. This study includes four (4) stages which project planning, data collection, data acquisition, and result and analysis. The benefit of this study JKR and JUPEM can implement GPR scanning to detect the volume of water table and prevent development any area that has high water table especially at hillside to avoid landslide.